An intensive personalised support approach to treating individuals with psychosis and co-morbid mild intellectual disability. (13th May 2016) - Raftery, M.; Burke, K.; Murray, N.; O'Duinn, O.; Murray, I.; Hallahan, B.
Abstract : Objectives: To evaluate the clinical benefits and associated cost effectiveness of an intensive personalised support (IPS) approach for clients suffering from psychosis and co-morbid mild intellectual disability (ID). Method: Four individuals with a psychotic disorder and co-morbid mild ID participated in an 18-month IPS rehabilitative intervention. Biopsychosocial measures were used to evaluate clinical effectiveness. A cost analysis was undertaken to examine the cost effectiveness of the intervention. Results: Reductions in psychopathology including anxiety symptoms were noted in all individuals. In addition, increased functioning and quality of life were demonstrated in all cases. Overall cost reductions were noted in inpatient care, accommodation and legal/emergency expenses. Conclusion: The IPS approach was clinically effective particularly in addressing individual's psychosocial needs, psychological functioning, daily living skills and overall quality of life. Costs had decreased for three of the four individuals, ranging from a 17% to 46% savings. The findings highlight that the intervention was cost effective in most cases at this early stage. However, further research is necessary in order to ascertain if cost savings occur over time.